Molecular Docking and 3-D QSAR Studies of Substituted 2,2-Bisaryl-Bicycloheptanes as Human 5-Lipoxygenase-Activating Protein (FLAP) Inhibitors - Ma, X.; Zhou, L.; Zuo, Zhili; Liu, J.; Yang, M.; Wang, R. (Wiley, 2008)
Leukotrienes have been shown to be involved in a variety of diseases such as cardiovascular diseases, cancer, asthma, ulcerative colitis, and rhinitis. 5-Lipoxygenase-Activating Protein (FLAP) was found to be a key enzyme of leukotriene synthesis. Comparative Molecular Field Analysis (CoMFA) and molecular docking studies were carried out on a series of substituted 2,2-bisaryl-bicycloheptanes FLAP inhibitors. The docking results provided a reliable conformational alignment scheme for 3-D QSAR model. Based on the docking conformations, highly predictive CoMFA model was performed with a leave-one-out cross-validated q2 of 0.651. The noncross-validated analysis with four optimum components revealed a conventional r2 value of 0.972, F=175.674, and an estimated standard error of 0.169. The predictive ability of this model was validated by the testing set with a conventional r2 value of 0.920. The analyses may be used to design more potent FLAP inhibitors and predict their activities prior to synthesis.